Letters and letter writing - Arzt-Grabner, Peter (Papyri and the New Testament, 2023)
New Testament letters are compared with private, business, and administrative letters of Greco-Roman antiquity and analyzed against this background. More than 11,800 Greek and Latin letters - preserved on papyrus, potsherds, and tablets from Egypt, Israel, Asia Minor, North Africa, Britain, and Switzerland - have been edited so far. Among them are not only short notes by writers with poor writing skills, but also extensive letters and correspondences from highly educated authors. They testify to the literary skills of Paul of Tarsus, who knew how to make excellent use of epistolary formulas and even introduced new variations. They also show that some New Testament letters clearly fall outside the framework of standard epistolography, raising new questions about their authors and their genre. The introductions and discussions offered in this volume reflect the current state of the art and present new research results. The volume also presents over 130 papyrus and ostracon letters newly translated in their entirety